Do High Job Demands Increase Intrinsic Motivation or Fatigue or Both? The Role of Job Control and Job Social Support - Yperen, Nico W. Van; Hagedoorn, Mariët (Academy of Management Journal, 2003)
In this study, we used Karasek's demand-control-support model to determine whether either job control or job social support or both can reduce signs of fatigue and simultaneously enhance intrinsic motivation among employees facing high job demands. Survey data on 555 nurses suggest that job control in particular reduces fatigue in highly demanding jobs, whereas high levels of instrumental support produce elevated levels of intrinsic motivation, regardless of the level of job control and job demands.